On three cultivated subspecies of pea (Pisum sativum L.) - O. E. Kosterin (Вавиловский журнал генетики и селекции)
The common pea (Pisum sativum L.) is an important crop characterised by high diversity, taxonomic ﬁxation of which may be important for selection as it attracts attention to the taxa recognised, although this recognition can be poorly justiﬁed. Two subspecies of the common pea, traditionally recognised in Russian botanical and genetical literature, Pisum sativum L. subsp. transcaucasicum Makasheva from Transcaucasia and Pisum sativum L. subsp. asiaticum Govorov from Anterior and Central Asia and North Africa, are considered, as well as their diagnostic characters and arguments in favour of their subspeciﬁc status. P. sativum subsp. transcaucasicum is characterised by small seeds, three pairs of small diamond-shaped leaﬂets, vigorous branching and full reproductive compatibility with Pisum sativum L. subsp. sativum and has a very limited range in Georgia. As a very local landrace it hardly deserves a subspeciﬁc status, however it is reasonable to consider it as a variety, Pisum sativum L. subsp. sativum var. transcaucasicum (Makasheva) Kosterin comb. nov. The subspecies P. sativum subsp. asiaticum practically misses diagnostic characters which are limited to small ﬂowers with presence of some ﬂavonoid pigmentation in the corolla. In fact, this subspecies has accumulated very diverse landraces from most of the Old World. Absence of reliable diagnostic characters makes it impossible to recognise this subspecies. Thus, P. sativum subsp. asiaticum is a later synonym of P. sativum subsp. sativum, to which all cultivated representatives of P. sativum L. should be attributed. A peculiar form traditionally cultivated in Egypt was described as the species Pisum jomardii Schrank and subsequently considered also in the ranks of subspecies and variety; it would better be considered as Pisum sativum L. subsp. sativum var. jomardii (Schrank) Govorov.